Production, Decomposition Rate and Identification of Bacteria on Avicennia alba Litter in the Coastal Zone Kuala Indragiri Riau Province - Simanjuntak, Ida Rahayu; Yoswaty, Dessy; ', Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
A research on the production, decomposition rate and identification of bacteria on Avicennia alba litter in the coastal zone Kuala Indragiri, Riau Province. This research was aimed to observe the contribution of mangrove forests in the productivity for surrounding environment and conducted from December 2014-March 2015. The litter production was calculated by using litter-trap. Sample was collected once in every 15 days during 45 days of observation. The litterfall was oven-dried and weighed. The result showed that avarage production of litterfall of A. alba in all station was 297.696 g/m2/45days (fresh weight) and 189.763 g/m2/45days (dry weight). The average total shrinking dry weight of litterfall leaf /day was at 0.13225 g/day or 1.3225 %/day. The average reduction dry weight of A. alba litterfall in every station was 7.848 g during 45 days of observation with a percentage value of the decomposed litterfall weight of 78.480% or 0,523 g/day, with final result of litterfall dry weight is 2,152 g. Seven types of bacterial colonies were identified on each station and consisted of Bacillus sp (2), Micrococcus sp, Xanthomonas sp, Pseudomonas sp, Vibrio sp and Escherichia sp.Keywords: Avicennia alba, litter, production, decomposition rate, bacteria, Kuala Indragiri